Darek and Rantau: an Identity through Diglossia - Hafiz Awlia Ramadhan (Antropologi Indonesia, 2016)
Through language, conceptions of self and the cultural knowledge of a society can be understood as interaction takes place. Observations and in-depth interviews were conducted to get descriptive results to explain the emic point of view about the dialects used and the dialects of other groups of people. The data was then analyzed with relevant theory and concepts, to get an understanding of the positions of dialects in communication events. By applying their cultural knowledge, peoples of Darek and Rantau, sub-groups in the larger Minangkabau ethnic group, in several contexts use dialects as indicators of another person’s identity. The difference in their cultural knowledge has given each dialect it’s own usage and view in their respective societies.Keywords : Code-switching, Diglossia, Identity, Lingua Franca, Linguistic Anthropology